2011
DOI: 10.1103/physreve.83.036117
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the scaling law in human mobility: Hierarchy of traffic systems

Abstract: Uncovering the mechanism leading to the scaling law in human trajectories is of fundamental importance in understanding many spatiotemporal phenomena. We propose a hierarchical geographical model to mimic the real traffic system, upon which a random walker will generate a power-law travel displacement distribution with exponent -2. When considering the inhomogeneities of cities' locations and attractions, this model reproduces a power-law displacement distribution with an exponential cutoff, as well as a scali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 28 publications
(30 reference statements)
5
74
0
Order By: Relevance
“…This simulation result is based on two ingredients of the model: the structure of the hierarchical purpose clusters and the individual preferential behavior. Indeed, the underlying geographical structure has a significant influence on the mode and/or distance of human travel; for instance, most people would probably like to travel the short distances to neighboring places by car whereas some people might prefer to travel long distances to far places by flying, and this argument has also been suggested by other studies [2,18]. On the other hand, the individual preferential behavior reflects Figure 11.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This simulation result is based on two ingredients of the model: the structure of the hierarchical purpose clusters and the individual preferential behavior. Indeed, the underlying geographical structure has a significant influence on the mode and/or distance of human travel; for instance, most people would probably like to travel the short distances to neighboring places by car whereas some people might prefer to travel long distances to far places by flying, and this argument has also been suggested by other studies [2,18]. On the other hand, the individual preferential behavior reflects Figure 11.…”
Section: Discussionmentioning
confidence: 58%
“…In this respect, we come up with another assumption: that the human preferential selection of available resources might also have a non-negligible influence on the mobility pattern. Our assumptions seem to be more similar to the hypotheses given by [2] and [18] than the others [3,19]. This paper thereby sets up two steps for verifying these assumptions.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The authors also propose a new model to characterize human mobility patterns [20]. Han et al [21] demonstrate that the scaling law in human mobility could be explained by hierarchy of the traffic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Guimera et al [25] showed that the worldwide air traffic network was a scale-free and small world network. Wang et al [26] proposed a hierarchical geographical model to mimic a real traffic system, upon which a random walk generates a power-law-like travel displacement distribution with tunable exponent. Li and Cai [16] showed that the topological structure of the air traffic network of China (ANC) had two key characteristics of smallworld networks, a short average path-length and a high degree of clustering.…”
mentioning
confidence: 99%